ETR : Blueprint : Le Calme Smart Diffuser / Fauzan Haziq Mardin ... [et al.] - Mardin, Fauzan Haziq; Ahmad Rohimin, Ika Cemalia; Kamal Ramlee, Kamalea Amaleena Farhana; Makhdar, Siti Zulaikha (2019)
The product to be developed is Le Calme Smart Diffuser. The aromatherapy helps the user to wake up, wind down or concentrate are emitted when the emotional intelligence sensor detect changes of body temperature at just the rjght time by the Le Calme smart diffuser, which combines aromatherapy with the Internet of things. However, the normal oil diffuser only capable of diffusing aromatherapy whereby the user have to manually add the essential oil. Therefore, the team is developing Le Calme smart diffuser, a diffuser that senses environment tension to reduce stressful minds for those having problems with stress working environment and want a better quality of living via voice control and phone app with the detection through emotional intelligence sensor.